Ultra-high performance concrete and preparation method and application thereof

By using the combined doping technology of gamma-phase alumina and graphene slurry in ultra-high performance concrete, the densified structure is formed, which solves the problem of existing ultra-high performance concrete prone to burst under high temperature conditions, and significantly improves its high temperature resistance.

CN116217178BActive Publication Date: 2025-03-25ZHEJIANG INST OF COMM CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310281981.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-03-25
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete is prone to burst and peeling under high temperature conditions, affecting the safety and service life of the building structure.

Method used

Ultra-high performance concrete formulas including inorganic cementitious materials, sand, gamma-phase alumina, graphene slurry, composite fibers and water are adopted, and through specific preparation methods, the composite doping technology of graphene slurry and gamma-phase alumina is used to form a densified structure to improve the high temperature resistance of concrete.

Benefits of technology

It significantly improves the mechanical properties of ultra-high performance concrete at high temperatures, delays or suppresses the expansion of micropores and cracks caused by high temperatures, ensures the high temperature resistance of the material, and is suitable for building structures in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116217178B_ABST
    Figure CN116217178B_ABST
Patent Text Reader

Abstract

The present invention provides an ultra-high performance concrete and a preparation method and application, specifically relating to the field of concrete technology. The ultra-high performance concrete includes inorganic cementitious materials, sand, γ-phase alumina, graphene slurry, composite fibers and water; wherein the composite fibers include steel fibers and polyoxymethylene fibers. The ultra-high performance concrete provided by the present invention has excellent high temperature resistance, with almost no loss of residual compressive strength after high temperature of 600°C, and only about 50% loss of residual compressive strength after high temperature of 1000°C, and is suitable for special scenarios with high requirements for high temperature resistance of materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to an ultra-high performance concrete and a preparation method and application thereof. Background Art

[0002] Ultra-high performance concrete is a new type of cement-based composite material designed and prepared based on the principles of the most compact particle packing, water-cement ratio less than 0.25, and fiber reinforcement. It has the characteristics of ultra-high strength, toughness, and durability, and has gradually become a popular choice for construction in the fields of bridges, railways, and buildings. Ultra-high performance concrete is mostly used in important components or key nodes of building structures. Building structures are inevitably subject to sudden disasters such as fire during their service. The dense microstructure and low permeability of ultra-high performance concrete make it extremely prone to cracking and spalling under high temperature conditions, which directly affects the safety and service life of building structures.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] One of the purposes of the present invention is to provide an ultra-high performance concrete, aiming to solve the technical problem in the prior art that ultra-high performance concrete is not resistant to high temperatures, which affects the safety and service life of building structures.

[0005] A second object of the present invention is to provide a method for preparing ultra-high performance concrete.

[0006] A third object of the present invention is to provide an application of ultra-high performance concrete in the inner wall of a kiln in thermal equipment or in a temporary dry storage facility for spent fuel in a nuclear power plant.

[0007] In order to solve the above technical problems, the present invention particularly adopts the following technical solutions:

[0008] A first aspect of the present invention provides an ultra-high performance concrete comprising an inorganic gelling material, sand, γ-phase alumina, graphene slurry, composite fibers and water;

[0009] Wherein, the composite fiber comprises steel fiber and polyoxymethylene fiber;

[0010] The inorganic gelling material includes cement, silica fume and inorganic functional powder;

[0011] The inorganic functional powder includes at least one of metakaolin, fly ash microbeads and limestone powder.

[0012] Furthermore, additives are included, and the additives include at least one of a water reducing agent, a defoaming agent and a swelling agent.

[0013] Furthermore, in parts by weight, it includes 1000 parts of inorganic gelling material, 700 parts to 900 parts of sand, 14 parts to 30 parts of γ-phase alumina, 0.2 parts to 0.5 parts of graphene slurry, 130 parts to 150 parts of composite fibers and 180 parts to 200 parts of water.

[0014] Preferably, in the composite fiber, the weight ratio of the steel fiber to the polyoxymethylene fiber is 100:3-5.

[0015] Furthermore, the average particle size of the γ-phase alumina is 10 μm-50 μm.

[0016] Preferably, the steel fiber has a diameter of 0.1 mm-0.3 mm, a length of 15 mm-20 mm, and a tensile strength greater than 2300 MPa.

[0017] Preferably, the polyoxymethylene fiber has a diameter of 0.1 mm to 0.3 mm and a length of 5 mm to 15 mm.

[0018] Furthermore, the graphene slurry includes at least one of graphene oxide slurry, multilayer graphene slurry and graphene sulfide slurry.

[0019] Preferably, the solid content of the graphene sulfide slurry is 5%-15%.

[0020] Preferably, the average particle size of the graphene sulfide is 50 μm-100 μm.

[0021] Preferably, the sulfide graphene sheet has a thickness of 1 nm to 2 nm.

[0022] Furthermore, the inorganic gelling material is cement, silica fume, metakaolin, fly ash microbeads and limestone powder.

[0023] Preferably, in the inorganic gelling material, the weight ratio of cement, silica fume, metakaolin, fly ash microbeads and limestone powder is 100:13-15:7-9:4-6:4-6.

[0024] Preferably, the average particle size of the silica fume is 0.1 μm-0.5 μm, and the specific surface area is 15 m 2 / g-20m 2 / g, SiO2 mass fraction is greater than 90%.

[0025] Preferably, the average particle size of the metakaolin is 1 μm-5 μm, and the specific surface area is 10 m 2 / g-20m 2 / g, the total mass fraction of SiO2 and Al2O3 is greater than 90%.

[0026] Preferably, the average particle size of the fly ash microbeads is 5 μm-10 μm, and the density is greater than 2 g / cm 3 -3g / cm 3 , SiO2 mass fraction is greater than 40%.

[0027] Preferably, the average particle size of the limestone powder is 3 μm-8 μm, and the density is greater than 2 g / cm 3 -3g / cm 3 , CaO mass fraction is greater than 50%.

[0028] Preferably, the sand comprises quartz sand and / or river sand.

[0029] Preferably, the particle size of the sand is in the range of 20 mesh to 70 mesh.

[0030] Furthermore, in terms of weight, the additives include 10-12 parts of a water reducing agent, 1-3 parts of a defoaming agent, and 35-40 parts of a swelling agent.

[0031] The second aspect of the present invention provides a method for preparing the ultra-high performance concrete, comprising the following steps:

[0032] A. Add γ-phase alumina to graphene slurry and stir, then add 1 / 5-1 / 2 of water to disperse evenly to obtain a γ-phase alumina / graphene solution;

[0033] B. uniformly mixing the inorganic gelling material, sand and optional additives to obtain a dry mix;

[0034] C. adding the γ-phase alumina / graphene solution obtained in step A and the remaining water to the dry mixture obtained in step B and stirring, and then adding the composite fiber and stirring evenly to obtain an ultra-high performance concrete slurry;

[0035] D. pouring the ultra-high performance concrete slurry to obtain the ultra-high performance concrete.

[0036] Furthermore, in step A, the dispersing includes ultrasonic dispersing.

[0037] The third aspect of the present invention provides the use of the ultra-high performance concrete in the inner wall of a kiln in a thermal equipment or in a temporary dry storage facility for spent fuel in a nuclear power plant.

[0038] Compared with the prior art, the present invention has at least the following beneficial effects:

[0039] The ultra-high performance concrete provided by the present invention uses graphene slurry to improve the micro-density of hydration products in the process of hydration of inorganic cementitious materials, thereby optimizing the pore structure of ultra-high performance concrete; the hydration products of γ-phase alumina and inorganic cementitious materials react with volcanic ash to form secondary hydration products, which further fill the pores of ultra-high performance concrete; the hydration products of graphene slurry and γ-phase alumina when added have different action mechanisms, and the two can further form a densified structure by working together, delaying or inhibiting the expansion of micropores and cracks caused by high temperature, thereby improving the mechanical properties of ultra-high performance concrete under high temperature. The composite fiber used has good dispersibility, high strength and elastic modulus, and produces a positive mixing effect after addition, ensuring the high fluidity, high strength and high toughness of the ultra-high performance concrete slurry; in addition, polyoxymethylene fiber can form three-dimensional randomly distributed channels after high-temperature melting, which is conducive to the escape of water vapor to avoid the occurrence of high-temperature bursting, thereby improving the high temperature resistance of ultra-high performance concrete.

[0040] The compressive strength of common ultra-high performance concrete materials (reinforced with steel fibers) is significantly reduced after being subjected to a high temperature of 600°C, and the compressive strength loss is as high as 80% after being subjected to a high temperature of 800°C. The ultra-high performance concrete provided by the present invention has excellent high temperature resistance, and the residual compressive strength after being subjected to a high temperature of 600°C is almost unchanged, and the residual compressive strength after being subjected to a high temperature of 1000°C is only lost by about 50%, which is suitable for special scenarios with high requirements for the high temperature resistance of materials.

[0041] The preparation method provided by the invention has simple and continuous process, high mechanization degree and is suitable for large-scale industrial production.

[0042] The application of the ultra-high performance concrete provided by the present invention provides ultra-high performance concrete with higher heat resistance for the inner wall of the kiln in thermal equipment or the temporary dry storage facility for spent fuel in a nuclear power plant, promotes the development of ultra-high performance concrete towards high safety and long life, and promotes the rapid development of the downstream industrial chain. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 The appearance of the ultra-high performance concrete obtained in Example 4 before (a) and after (b) the compression test;

[0045] Figure 2The appearance of the ultra-high performance concrete obtained in Example 5 before (a) and after (b) the compression test;

[0046] Figure 3 The appearance of the ultra-high performance concrete obtained in Example 6 before (a) and after (b) the compression test;

[0047] Figure 4 The appearance of the ultra-high performance concrete obtained in Example 7 before (a) and after (b) the compression test;

[0048] Figure 5 The appearance of the ultra-high performance concrete obtained in Comparative Example 1 before (a) and after (b) the compression test;

[0049] Figure 6 The appearance of the ultra-high performance concrete obtained in Comparative Example 2 before (a) and after (b) the compression test;

[0050] Figure 7 This is a microstructural characteristic diagram of the fiber pores of the ultra-high performance concrete obtained in Example 7;

[0051] Figure 8 This is a microstructure characteristic diagram of the fiber pores of the ultra-high performance concrete obtained in Comparative Example 1;

[0052] Fig. 9 This is a microstructural characteristic diagram of the ultra-high performance concrete matrix obtained in Example 7;

[0053] Fig.10 This is a microstructural characteristic diagram of the ultra-high performance concrete matrix obtained in Comparative Example 2. DETAILED DESCRIPTION

[0054] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The components of the embodiments of the present invention described and shown herein can be arranged and designed in various different configurations.

[0055] A first aspect of the present invention provides an ultra-high performance concrete comprising an inorganic gelling material, sand, γ-phase alumina, graphene slurry, composite fibers and water;

[0056] Wherein, the composite fiber comprises steel fiber and polyoxymethylene fiber;

[0057] The inorganic gelling material includes cement, silica fume and inorganic functional powder;

[0058] The inorganic functional powder includes at least one of metakaolin, fly ash microbeads and limestone powder.

[0059] The ultra-high performance concrete provided by the present invention uses graphene slurry to improve the micro-density of the hydration product during the hydration process of the inorganic cementitious material, thereby optimizing the pore structure of the ultra-high performance concrete; the hydration product of the γ-phase alumina reacts with the hydration product of the inorganic cementitious material to form a secondary hydration product, which further fills the pores of the ultra-high performance concrete; the hydration product and action mechanism of the graphene slurry and the γ-phase alumina are different, and the combined action of the two can further improve the mechanical properties of the ultra-high performance concrete under high temperature. The addition of composite fibers ensures the high fluidity, high strength and high toughness of the ultra-high performance concrete slurry, and at the same time improves the high temperature resistance of the ultra-high performance concrete. The ultra-high performance concrete provided by the present invention has excellent high temperature resistance, and the residual compressive strength after the high temperature of 600°C is almost not lost, and the residual compressive strength after the high temperature of 1000°C is only lost by about 50%, which is suitable for special scenarios with high requirements for the high temperature resistance of materials.

[0060] γ-phase Al2O3 is an active oxide with the characteristics of large specific surface area and high activity, which can improve the pore structure of ultra-high performance concrete.

[0061] Polyoxymethylene fiber is an organic synthetic fiber with excellent comprehensive performance and low relative density (1.41g / cm 3 ), high tensile strength (967MPa~1175MPa), good alkali resistance (99%), long-term stability, good wear resistance, etc. There are a large number of ether bonds in its molecular structure, which has good compatibility with inorganic materials and high bonding strength, and can improve the toughness and crack resistance of ultra-high performance concrete.

[0062] Furthermore, additives are included, and the additives include at least one of a water reducing agent, a defoaming agent and a swelling agent.

[0063] In some embodiments of the present invention, the water reducing agent is a polycarboxylic acid white powder (water reduction rate greater than 30%), the defoaming agent is a polyether white powder, and the swelling agent is calcium sulfoaluminate or calcium oxide.

[0064] Furthermore, in parts by weight, it includes 1000 parts of inorganic gelling material, 700 parts to 900 parts of sand, 14 parts to 30 parts of γ-phase alumina, 0.2 parts to 0.5 parts of graphene slurry, 130 parts to 150 parts of composite fibers and 180 parts to 200 parts of water.

[0065] In some embodiments of the present invention, in the ultra-high performance concrete, the weight percentage of inorganic cementitious materials is typically but not limited to 1000 parts; the weight percentage of sand is typically but not limited to 700 parts, 750 parts, 800 parts, 850 parts or 900 parts; the weight percentage of γ-phase alumina is typically but not limited to 14 parts, 18 parts, 22 parts, 26 parts or 30 parts; the weight percentage of graphene slurry is typically but not limited to 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts; the weight percentage of composite fibers is typically but not limited to 130 parts, 135 parts, 140 parts, 145 parts or 150 parts; the weight percentage of water is typically but not limited to 180 parts, 185 parts, 190 parts, 195 parts or 200 parts.

[0066] Preferably, in the composite fiber, the weight ratio of steel fiber to polyoxymethylene fiber is 100:3-5. When the weight ratio of steel fiber to polyoxymethylene fiber is greater than 100:3, the effect of improving the high temperature resistance of ultra-high performance concrete is not significant; when the weight ratio of steel fiber to polyoxymethylene fiber is less than 100:5, the effect of strengthening and toughening ultra-high performance concrete is not significant. In some embodiments of the present invention, the weight ratio of steel fiber to polyoxymethylene fiber is typically but not limited to 100:3, 100:4 or 100:5.

[0067] Further, the average particle size of the γ-phase alumina is 10 μm-50 μm. In some embodiments of the present invention, the average particle size of the γ-phase alumina is typically but not limited to 10 μm, 20 μm, 30 μm, 40 μm or 50 μm.

[0068] Preferably, the steel fiber has a diameter of 0.1 mm-0.3 mm, a length of 15 mm-20 mm, and a tensile strength greater than 2300 MPa.

[0069] Preferably, the polyoxymethylene fiber has a diameter of 0.1 mm to 0.3 mm and a length of 5 mm to 15 mm.

[0070] In some embodiments of the present invention, the length of the polyoxymethylene fiber is selected to be a compound of 14 mm and 6 mm, and the weight ratio of these two fibers is preferably (2-4): (0-1).

[0071] Furthermore, the graphene slurry includes at least one of graphene oxide slurry, multilayer graphene slurry and graphene sulfide slurry.

[0072] As a derivative of graphene, graphene oxide has a sp 2The hybridized carbon atom plane is distributed with different numbers of oxygen-containing functional groups such as hydroxyl and carboxyl. Due to the presence of oxygen functional groups such as hydroxyl, carboxyl and epoxy, graphene oxide is easier to disperse in aqueous solutions and other organic solvents than graphene sheets. Sulfurized graphene can be obtained by sulfurizing (oxidized) graphene and a vulcanizing agent in a solvent, and the dispersibility of graphene can be further improved by sulfurization.

[0073] As a kind of graphene derivative, multilayer graphene is basically composed of single-layer carbon atom planar structure graphene stacked together. The carbon atoms are connected by π-π bonds, and the bonding mode is sp 2 Hybridization. The π-π bonds between carbon atoms give multilayer graphene very ideal mechanical properties and structural rigidity. It should be distinguished that there is a certain difference between multilayer graphene and graphene nanosheets, although the latter is also made of stacked graphene.

[0074] Preferably, the solid content of the graphene sulfide slurry is 5%-15%. In some embodiments of the present invention, the solid content of the graphene sulfide slurry is typically but not limited to 5%, 7%, 9%, 11%, 13% or 15%.

[0075] Preferably, the average particle size of the sulfided graphene is 50 μm-100 μm. In some embodiments of the present invention, the average particle size of the sulfided graphene is typically but not limited to 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm.

[0076] Preferably, the sulfide graphene sheet has a thickness of 1 nm to 2 nm.

[0077] Furthermore, the inorganic gelling material is cement, silica fume, metakaolin, fly ash microbeads and limestone powder.

[0078] Preferably, in the inorganic cementitious material, the weight ratio of cement, silica fume, metakaolin, fly ash microbeads and limestone powder is 100:13-15:7-9:4-6:4-6. In some embodiments of the present invention, the weight ratio of cement, silica fume, metakaolin, fly ash microbeads and limestone powder is typically but not limited to 100:13:7:4:4, 100:15:7:4:4, 100:13:9:4:4, 100:15:9:4:4, 100:13:7:6:4, 100:15:7:6:4, 100:13:7:4:6 or 100:15:7:4:6.

[0079] Preferably, the average particle size of the silica fume is 0.1 μm-0.5 μm, and the specific surface area is 15 m 2 / g-20m 2 / g, SiO2 mass fraction is greater than 90%.

[0080] Preferably, the average particle size of the metakaolin is 1 μm-5 μm, and the specific surface area is 10 m 2 / g-20m 2 / g, the total mass fraction of SiO2 and Al2O3 is greater than 90%.

[0081] Preferably, the average particle size of the fly ash microbeads is 5 μm-10 μm, and the density is greater than 2 g / cm 3 -3g / cm 3 , SiO2 mass fraction is greater than 40%.

[0082] Preferably, the average particle size of the limestone powder is 3 μm-8 μm, and the density is greater than 2 g / cm 3 -3g / cm 3 , CaO mass fraction is greater than 50%.

[0083] Preferably, the sand comprises quartz sand and / or river sand.

[0084] Preferably, the particle size of the sand is in the range of 20 mesh to 70 mesh.

[0085] Furthermore, in terms of weight, the additives include 10-12 parts of a water reducing agent, 1-3 parts of a defoaming agent, and 35-40 parts of a swelling agent.

[0086] The second aspect of the present invention provides a method for preparing the ultra-high performance concrete, comprising the following steps:

[0087] A. Add γ-phase alumina to graphene slurry and stir, then add 1 / 5-1 / 2 of water to disperse evenly to obtain a γ-phase alumina / graphene solution;

[0088] B. uniformly mixing the inorganic gelling material, sand and optional additives to obtain a dry mix;

[0089] C. adding the γ-phase alumina / graphene solution obtained in step A and the remaining water to the dry mixture obtained in step B and stirring, and then adding the composite fiber and stirring evenly to obtain an ultra-high performance concrete slurry;

[0090] D. pouring the ultra-high performance concrete slurry to obtain the ultra-high performance concrete.

[0091] The preparation method provided by the invention has simple and continuous process, high mechanization degree and is suitable for large-scale industrial production.

[0092] Furthermore, in step A, the dispersing includes ultrasonic dispersing.

[0093] The third aspect of the present invention provides the use of the ultra-high performance concrete in the inner wall of a kiln in a thermal equipment or in a temporary dry storage facility for spent fuel in a nuclear power plant.

[0094] The application of the ultra-high performance concrete provided by the present invention provides ultra-high performance concrete with higher heat resistance for the inner wall of the kiln in thermal equipment or the temporary dry storage facility for spent fuel in a nuclear power plant, promotes the development of ultra-high performance concrete towards high safety and long life, and promotes the rapid development of the downstream industrial chain.

[0095] In the following, some embodiments of the present invention are described in detail in conjunction with the embodiments. In the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. The raw materials used in the present invention can be obtained by commercial purchase unless otherwise specified.

[0096] The material specifications used in the following examples and comparative examples are as follows:

[0097] The specific surface area of ​​silica fume is greater than 18m 2 / g and the SiO2 mass fraction is greater than 94%.

[0098] The specific surface area of ​​metakaolin is about 15m 2 / g and the total mass fraction of SiO2 and Al2O3 is greater than 94%.

[0099] The density of fly ash microbeads is 2.44g / cm 3 , the average particle size is about 8μm and the SiO2 mass fraction is greater than 50%.

[0100] The density of limestone powder is 2.53g / cm 3 , the average particle size is about 5 μm and the CaO mass fraction is greater than 50%.

[0101] γ-phase alumina is in the form of white powder with an average particle size of about 30 μm.

[0102] The solid content of the sulfide graphene slurry is an aqueous solution of 10%, the average particle size of the sulfide graphene is 50 μm-100 μm, and the thickness is 1 nm-2 nm.

[0103] Example 1

[0104] The present embodiment provides an ultra-high performance concrete, comprising the following components: 1 kg of inorganic cementitious material, 0.8 kg of 20-70 mesh quartz sand, 0.014 kg of γ-phase alumina, 0.0003 kg of sulfide graphene slurry, 0.001 kg of polycarboxylic acid powder water reducer, 0.002 kg of polyether powder defoamer, 0.038 kg of calcium oxide expansion agent, 0.13 kg of composite fiber, and 0.19 kg of water.

[0105] The inorganic cementitious material is composed of a mixture of 0.76kg PO42.5 silicate cement, 0.11kg silica fume, 0.06kg metakaolin, 0.03kg fly ash beads and 0.04kg limestone powder.

[0106] The composite fiber consists of 0.125 kg steel fiber and 0.005 kg polyoxymethylene fiber.

[0107] The steel fiber has a diameter of about 0.2 mm, a length of 18 mm, and a tensile strength of more than 2500 MPa. The polyoxymethylene fiber has a diameter of 0.2 mm, a length of 14 mm, and a weight ratio of 6 mm of 3:1.

[0108] The specific preparation process is as follows:

[0109] 1. Premix inorganic gelling material, sand, water reducing agent, defoaming agent and expansion agent for about 15 minutes to obtain ultra-high performance concrete dry mix;

[0110] 2. Add γ-alumina powder to the graphene sulfide aqueous solution and stir for 1 min. Then add about 1 / 2 of the stirring water to dilute it and perform ultrasonic dispersion for about 1 h to obtain a γ-alumina / graphene sulfide solution.

[0111] 3. Add the prepared γ-phase alumina / graphene sulfide solution and the remaining water into the ultra-high performance concrete dry mix and stir for 4 minutes. Then evenly sprinkle the steel fiber and polyoxymethylene fiber and continue stirring for 2 minutes to obtain the ultra-high performance concrete fresh slurry. No vibration is required during the whole process.

[0112] Example 2

[0113] The present embodiment provides an ultra-high performance concrete, comprising the following components: 1 kg of inorganic cementitious material, 0.9 kg of 20-70 mesh quartz sand, 0.03 kg of γ-phase alumina, 0.0005 kg of sulfide graphene slurry, 0.012 kg of polycarboxylic acid powder water reducer, 0.002 kg of polyether powder defoamer, 0.035 kg of calcium oxide expansion agent, 0.14 kg of composite fiber, and 0.2 kg of water.

[0114] The inorganic cementitious material is composed of a mixture of 0.757kg PO 42.5 silicate cement, 0.098kg silica fume, 0.053kg metakaolin, 0.046kg fly ash beads and 0.046kg limestone powder.

[0115] The composite fiber is composed of 0.13kg steel fiber and 0.01kg polyoxymethylene fiber.

[0116] The steel fiber has a diameter of about 0.2 mm, a length of 16 mm, and a tensile strength of more than 2500 MPa.

[0117] The diameter of the polyoxymethylene fiber is 0.2 mm, and the weight ratio of the length is 14 mm and 6 mm is 2:1.

[0118] The preparation method is the same as Example 1.

[0119] Example 3

[0120] The present embodiment provides an ultra-high performance concrete, comprising the following components: 1 kg of inorganic cementitious material, 0.9 kg of 20-70 mesh quartz sand, 0.02 kg of γ-phase alumina, 0.0004 kg of sulfide graphene slurry, 0.012 kg of polycarboxylic acid powder water reducer, 0.002 kg of polyether powder defoamer, 0.04 kg of calcium oxide expansion agent, 0.13 kg of composite fiber, and 0.2 kg of water.

[0121] The inorganic cementitious material is composed of a mixture of 0.775kg PO 42.5 silicate cement, 0.1kg silica fume, 0.054kg metakaolin, 0.039kg fly ash beads and 0.031kg limestone powder.

[0122] The composite fiber is composed of 0.123kg steel fiber and 0.007kg polyoxymethylene fiber.

[0123] The steel fiber has a diameter of about 0.2 mm, a length of 18 mm, and a tensile strength of more than 2500 MPa.

[0124] The diameter of the polyoxymethylene fiber is 0.2 mm, and the weight ratio of the length is 14 mm and 6 mm is 4:1.

[0125] The preparation method is the same as Example 1.

[0126] Example 4

[0127] The present embodiment provides an ultra-high performance concrete, including the following components: 1 kg of inorganic cementitious material, 0.85 kg of 20-70 mesh quartz sand, 0.025 kg of γ-phase alumina, 0.00045 kg of sulfide graphene slurry, 0.012 kg of polycarboxylic acid powder water reducer, 0.002 kg of polyether powder defoamer, 0.037 kg of calcium oxide expansion agent, 0.15 kg of composite fiber, and 0.2 kg of water.

[0128] The inorganic cementitious material is composed of a mixture of 0.775kg PO 42.5 silicate cement, 0.1kg silica fume, 0.054kg metakaolin, 0.039kg fly ash beads and 0.031kg limestone powder.

[0129] The composite fiber is composed of 0.143kg steel fiber and 0.007kg polyoxymethylene fiber.

[0130] The steel fiber has a diameter of about 0.2 mm, a length of 18 mm, and a tensile strength of more than 2500 MPa.

[0131] The polyoxymethylene fiber has a diameter of 0.2 mm and a length of 14 mm.

[0132] The preparation method is the same as Example 1.

[0133] Example 5

[0134] This embodiment provides an ultra-high performance concrete, and the raw materials and preparation method are the same as those in Embodiment 4.

[0135] Example 6

[0136] This embodiment provides an ultra-high performance concrete, and the raw materials and preparation method are the same as those in Embodiment 4.

[0137] Example 7

[0138] This embodiment provides an ultra-high performance concrete, and the raw materials and preparation method are the same as those in Embodiment 4.

[0139] Example 8

[0140] This embodiment provides an ultra-high performance concrete. The difference from Embodiment 4 is that graphene oxide slurry is used in the raw materials instead of graphene sulfide slurry, the solid content of the graphene oxide slurry is 10%, and other raw materials and preparation methods are the same as those in Embodiment 4, which will not be repeated here.

[0141] Example 9

[0142] This embodiment provides an ultra-high performance concrete, which is different from the embodiment 4 in that multi-layer graphene slurry is used in the raw materials to replace the sulfide graphene slurry, the solid content of the multi-layer graphene slurry is 10%, the particle size of the multi-layer graphene is 50 μm-100 μm, and the thickness is 1 nm-2 nm. Other raw materials and preparation methods are the same as those in the embodiment 4, and will not be repeated here.

[0143] Comparative Example 1

[0144] This comparative example provides an ultra-high performance concrete. Different from Example 4, the composite fiber consists of 0.123 kg of steel fiber and 0.007 kg of polyvinyl alcohol fiber.

[0145] The steel fiber has a diameter of about 0.2 mm, a length of 18 mm, and a tensile strength of more than 2500 MPa.

[0146] The diameter of the polyvinyl alcohol fiber is 0.2 mm, and the weight ratio of the length is 14 mm and 6 mm is 4:1.

[0147] Other raw materials and preparation methods are the same as those in Example 4 and will not be described again.

[0148] Comparative Example 2

[0149] This comparative example provides an ultra-high performance concrete. The difference from Example 4 is that no γ-phase alumina and sulfide graphene slurry are added to the raw materials. Other raw materials and preparation methods are the same as those in Example 4 and will not be described again.

[0150] Comparative Example 3

[0151] This comparative example provides an ultra-high performance concrete. The difference from Example 4 is that γ-phase alumina is not added to the raw materials. Other raw materials and preparation methods are the same as those in Example 4 and will not be described in detail here.

[0152] Comparative Example 4

[0153] This comparative example provides an ultra-high performance concrete. The difference from Example 4 is that no sulfide graphene slurry is added to the raw materials, and the other raw materials and preparation methods are the same as those in Example 4, which will not be repeated here.

[0154] Test example

[0155] The ultra-high performance concrete slurries obtained in Examples 1-9 and Comparative Examples 1-4 were subjected to the following performance tests, and the specific process is as follows:

[0156] 1. Pour the ultra-high performance concrete slurry into a cubic test mold with a side length of 100 mm. Each group of implementation (comparison) examples forms 6 cubic test blocks, which are placed in an indoor environment at 20°C and 60% humidity for curing for 1 day and then demolded. Then, they are moved into a standard curing room and cured to 28 days old, then the test pieces are taken out and placed in a ventilated and dry place to dry naturally for 24 hours.

[0157] 2. Three cubic test blocks in each implementation (comparative) example were directly subjected to compression test, and the other three cubic test blocks were subjected to compression test after high temperature burst test. The cubic compression test was carried out in accordance with the Standard for Test Methods of Mechanical Properties of Ordinary Concrete (GB / T 50081-2016), with the loading rate set at 1 MPa / s. The obtained data are recorded in Table 1.

[0158] In addition, each cubic specimen was weighed before and after high temperature treatment to determine the mass loss of the specimen during the heating process, and the data are recorded in Table 1.

[0159] 3. High temperature burst test: The remaining three cubic test blocks in each group of implementation (comparative) examples were placed in a resistance high temperature furnace for heating, and the heating rate was set to 10°C / min. After heating to the target temperature, the temperature was maintained for 3 hours, and then the resistance furnace was closed and naturally cooled to room temperature (about 6 hours) before the test pieces were taken out. The target temperature of Examples 1-4 was set to 600°C, the target temperatures of Examples 5-7 were set to 400°C, 800°C, and 1000°C, respectively, and the target temperatures of Examples 8-9 and Comparative Examples 1-4 were all 1000°C.

[0160] 4. Microscopic test: In order to further explore the high temperature action mechanism of ultra-high performance concrete materials, samples were taken from Example 7 and Comparative Examples 1-2 after high temperature action, and the microstructural characteristics of the ultra-high performance concrete materials were observed using a microscope.

[0161] Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 The appearance pictures of the ultra-high performance concrete before (a in the figure) and after (b in the figure) the compression test respectively correspond to Example 5, Example 4, Example 6, Example 7, Comparative Example 1 and Comparative Example 2.

[0162] Depend on Figure 1 , Figure 2 , Figure 3 and Figure 4 It can be seen that the ultra-high performance concrete specimens prepared in Examples 4-7 did not experience high-temperature bursting. After high temperature, the specimens turned white or yellow, and the specimens were intact in shape, with a few microcracks and pores left by the melting of polyoxymethylene fibers on the surface. Figure 5 and Figure 6 It can be seen that the ultra-high performance concrete specimen prepared in comparative example 1 has a small amount of edge and corner chipping after high temperature, and the ultra-high performance concrete specimen prepared in comparative example 2 is also relatively complete after high temperature. The above specimens still maintain a certain degree of integrity after being damaged by pressure.

[0163] Table 1 shows the relevant test data of all ultra-high performance concrete specimens before and after high temperature. Each data is the average value of 3 specimens in each group, where the relative compressive strength ratio is the ratio of the residual compressive strength after high temperature to the compressive strength before high temperature.

[0164] Table 1

[0165]

[0166] It can be seen from Table 1 that the mass loss rate and relative compressive strength ratio of the ultra-high performance concrete specimens prepared in Examples 1-4 after high temperature action at 600°C are relatively close, indicating that the ultra-high performance concrete prepared in the preferred range of the formula of the present invention has good stability in high temperature resistance; compared with Examples 4-7, it can be seen that high temperature action at 400°C can improve the compressive properties of ultra-high performance concrete, while high temperature action above 600°C has an adverse effect on its compressive properties; compared with Examples 7-9, it can be seen that the type of graphene slurry has little effect on the high temperature resistance of ultra-high performance concrete, among which the effect of sulfide graphene is slightly better.

[0167] In addition, compared with Example 7, it can be seen that the residual compressive strength loss of the ultra-high performance concrete specimen prepared in Example 1 is more serious, which shows that compared with polyvinyl alcohol fiber, polyoxymethylene fiber has a better improvement effect on the high temperature resistance of ultra-high performance concrete; the residual compressive strength loss of the ultra-high performance concrete specimens prepared in Examples 2-4 is also more serious, indicating that the γ-phase alumina / sulfurized graphene co-doping technology can improve the high temperature resistance of ultra-high performance concrete.

[0168] Figure 7 , Figure 8 , Fig. 9 and Fig.10 Figure 2 shows the microstructure characteristics of some ultra-high performance concrete specimens. Figure 7 and Figure 8 Corresponding to the microstructure characteristic diagram of the fiber pores of the ultra-high performance concrete obtained in Example 7 and Comparative Example 1; Fig. 9 and Fig.10 Corresponding to the microstructural characteristic diagram of the ultra-high performance concrete matrix obtained in Example 7 and Comparative Example 2.

[0169] contrast Figure 7 and Figure 8 It can be seen that both polyoxymethylene fiber and polyvinyl alcohol fiber melted and left channels after high temperature exposure. Microcracks appeared in the channels left by polyvinyl alcohol fiber, while there were no cracks in the channels left by polyoxymethylene fiber. This shows that the melting of polyoxymethylene fiber caused less damage to the ultra-high performance concrete matrix, thus having higher residual compressive strength. Fig. 9 and Fig.10 It can be seen that the ultra-high performance concrete with γ-phase alumina / graphene sulfide added has a denser microstructure after experiencing high temperature, thereby improving its mechanical properties after high temperature.

[0170] In summary, the ultra-high performance concrete material prepared by the steel-polyoxymethylene fiber hybrid method and the γ-phase alumina / graphene sulfide composite mixing technology in the present invention has more excellent high temperature resistance.

[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ultra-high performance concrete for the inner wall of a kiln in thermal equipment or a temporary dry storage facility for spent fuel in a nuclear power plant, characterized in that: According to weight parts, it includes 1000 parts of inorganic gelling material, 700 parts to 900 parts of sand, 14 parts to 30 parts of γ-phase alumina, 0.2 parts to 0.5 parts of graphene slurry, 130 parts to 150 parts of composite fiber and 180 parts to 200 parts of water; Wherein, the composite fiber comprises steel fiber and polyoxymethylene fiber in a weight ratio of 100:3-5; The steel fiber has a diameter of 0.1 mm to 0.3 mm, a length of 15 mm to 20 mm, and a tensile strength greater than 2300 MPa; The polyoxymethylene fiber has a diameter of 0.1 mm to 0.3 mm and a length of 5 mm to 15 mm; The inorganic gelling material is cement, silica fume, metakaolin, fly ash microbeads and limestone powder in a weight ratio of 100:13-15:7-9:4-6:4-6.

2. The ultra-high performance concrete according to claim 1, characterized in that: The invention also includes additives, wherein the additives include at least one of a water reducing agent, a defoaming agent and a swelling agent.

3. The ultra-high performance concrete according to claim 1 or 2, characterized in that: The average particle size of the γ-phase alumina is 10 μm-50 μm.

4. The ultra-high performance concrete according to claim 1 or 2, characterized in that: The graphene slurry includes at least one of graphene oxide slurry, multilayer graphene slurry and graphene sulfide slurry.

5. The ultra-high performance concrete according to claim 4, characterized in that: The solid content of the graphene sulfide slurry is 5%-15%.

6. The ultra-high performance concrete according to claim 4, characterized in that: The average particle size of the sulfided graphene is 50 μm-100 μm.

7. The ultra-high performance concrete according to claim 4, characterized in that: The sheet thickness of the graphene sulfide is 1nm-2nm.

8. The ultra-high performance concrete according to claim 1 or 2, characterized in that: The average particle size of the silica fume is 0.1 μm-0.5 μm, and the specific surface area is 15 m 2 / g-20m 2 / g, SiO2 mass fraction is greater than 90%.

9. The ultra-high performance concrete according to claim 1 or 2, characterized in that: The average particle size of the metakaolin is 1 μm-5 μm, and the specific surface area is 10 m 2 / g-20m 2 / g, the sum of SiO2 and Al2O3 mass fractions is greater than 90%.

10. The ultra-high performance concrete according to claim 1 or 2, characterized in that: The average particle size of the fly ash microbeads is 5 μm-10 μm, and the density is 2 g / cm 3 -3g / cm 3 , SiO2 mass fraction is greater than 40%.

11. The ultra-high performance concrete according to claim 1 or 2, characterized in that: The average particle size of the limestone powder is 3 μm-8 μm, and the density is 2 g / cm 3 -3g / cm 3 , CaO mass fraction is greater than 50%.

12. The ultra-high performance concrete according to claim 1 or 2, characterized in that: The sand includes quartz sand and / or river sand.

13. The ultra-high performance concrete according to claim 1 or 2, characterized in that: The particle size of the sand ranges from 20 meshes to 70 meshes.

14. The ultra-high performance concrete according to claim 2, characterized in that: In terms of weight, the additives include 10-12 parts of a water reducing agent, 1-3 parts of a defoaming agent, and 35-40 parts of a swelling agent.

15. A method for preparing ultra-high performance concrete according to any one of claims 1 to 14, characterized in that: The following steps are involved: A. Add γ-phase alumina to graphene slurry and stir, then add 1 / 5-1 / 2 of water to disperse evenly to obtain a γ-phase alumina / graphene solution; B. uniformly mixing the inorganic gelling material, sand and optional additives to obtain a dry mix; C. adding the γ-phase alumina / graphene solution obtained in step A and the remaining water to the dry mix obtained in step B and stirring, and then adding the composite fiber and stirring evenly to obtain an ultra-high performance concrete slurry; D. pouring the ultra-high performance concrete slurry to obtain the ultra-high performance concrete.

16. The preparation method according to claim 15, characterized in that: In step A, the dispersing includes ultrasonic dispersing.

Citation Information

Patent Citations

  • Graphene oxide ultra-high performance concrete with low cement consumption and preparation method thereof

    CN111377687A

  • Fireproof and antiknock ultra-high performance concrete and preparation method thereof

    CN115784682A